LEVERAGING AUGMENTED REALITY (AR) LEARNING MEDIA INTEGRATED WITH ASSEMBLR EDU TO ENHANCE EFL STUDENTS’ VOCABULARY RETENTION - Siti Ayu Surayya; Baiq Helmalya Roshita; Zahratul Fikni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary retention remains a significant challenge in learning English as a Foreign Language (EFL), especially in settings with limited language exposure. Conventional teaching methods are often less interactive and less effective at supporting long-term vocabulary retention. This study aims to determine the effect of Augmented Reality (AR) learning media integrated with Assemblr Edu on the vocabulary retention of EFL students at SMPN 1 Terara. This study used a one group pre-experimental design with a pre-test and post-test involving 30 eighth-grade students selected through cluster random sampling. Data were collected using a vocabulary retention test consisting of 20 items and were analyzed using descriptive statistics, the Kolmogorov-Smirnov and Shapiro-Wilk normality tests, a paired t-test, and Normalized Gain (N-Gain). The results showed that the students’ average score increased from 66.67 on the pre-test to 80.83 on the post-test, with an average difference of 14.17 points. The paired-sample t-test yielded a t-value (29) of 14.167, p = 0.000 (< 0.05), indicating a statistically significant difference between the pre-test and post-test scores, thereby rejecting the null hypothesis (H₀) and confirming the alternative hypothesis (H₁). The N-Gain analysis yielded an average score of 42.38% (medium category). These findings indicate that AR media integrated with Assemblr Edu is quite effective in improving EFL students’ vocabulary retention through interactive, contextual, and immersive learning experiences. Keywords: Augmented Reality, Assemblr Edu, EFL, Vocabulary Retention, Pre-Experimental.